Perencanaan dan Biaya Reklamasi pada Lahan Bekas Penambangan Batu Kapur di Front IV Bukit Karang Putih PT Semen Padang Kecamatan Lubuk Kilangan Kota Padang Provinsi Sumatera Barat - Muhammad Zaki; Yunasril Yunasril; Ansosry Ansosry (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. PT Semen Padang is a limestone mining company located in Bukit Karang Putih, Padang City, West Sumatra Province, which has a Front IV mining area located in the Indarung VI mining area. In the area there are ex-mining areas (areas A, B and C) covering an area of 3 hectares which have been reclaimed but are not well-organized, located west of Crusher VI. Many relatively steep cliffs, such as in area A with a slope of 42 ° - 61º, area B with a slope of 45° and area C with a slope of 58º. This situation has the potential for landslides and causes danger in the Mobile Crusher VI series. The level geometry in the reclamation area has 5 levels with different lengths, widths, heights and slopes, and has a single slope on the left and right. When it rains the water flow in the field if the Front IV area of 15.15 Ha leads to that area and will disrupt the production activities in Crusher VI and can cause erosion. Therefore, re-reclamation planning and design costs are needed. The reclamation plan starts from the land arrangement that starts from the upper land in the form of dredging, stockpiling and overburden material removal, as well as the formation of 10 terraces on the slope of the reclamation area with a tilted bench terrace at 3%. After that management of top soil and sub soil, planting cover crops, revegetation by planting trembesi trees, maintenance for the first 3 years, and calculating the costs that will be incurred by the company in the reclamation process. Based on calculations in the planning of reclamation of ex-mining land by means of revegetation, the total total cost is obtained at Rp. 2.855.627.367.Keywords:  Front IV, Crusher VI, Reclamation, Revegetation, Cost Design